2004
DOI: 10.1158/0008-5472.can-04-0863
|View full text |Cite
|
Sign up to set email alerts
|

P21Cip1 Is a Critical Mediator of the Cytotoxic Action of Thymidylate Synthase Inhibitors in Colorectal Carcinoma Cells

Abstract: We have demonstrated previously that interferon (IFN)-␥ sensitizes human colon carcinoma cell lines to the cytotoxic effects of 5-fluorouracil combined with leucovorin and to the thymidylate synthase inhibitor, ZD9331, dependent on thymineless stress-induced DNA damage, independent of p53. Here we demonstrate that the cyclin-dependent kinase (CDK) inhibitor p21Cip1 regulates thymineless stress-induced cytotoxicity in these cells. HCT116 wild-type (wt) and p53؊/؊ cells underwent apoptosis and loss in clonogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 45 publications
6
33
1
Order By: Relevance
“…Still, we cannot exclude the possibility that the inverse relation between p21 expression and response to gefitinib and chemotherapy was principally related to the effect of 5-FU and irinotecan rather than any interaction with gefitinib. However, in contrast to our findings, a recent review of 1,809 colorectal cancer cases in the published literature suggest that, overall, greater p21 expression predicted a greater responsiveness to fluoropyrimidine-based chemotherapy that did not include an EGFR inhibitor (28). We are unaware of any other study that has examined predictors of responsiveness to gefitinib-based therapy in patients with colorectal cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…Still, we cannot exclude the possibility that the inverse relation between p21 expression and response to gefitinib and chemotherapy was principally related to the effect of 5-FU and irinotecan rather than any interaction with gefitinib. However, in contrast to our findings, a recent review of 1,809 colorectal cancer cases in the published literature suggest that, overall, greater p21 expression predicted a greater responsiveness to fluoropyrimidine-based chemotherapy that did not include an EGFR inhibitor (28). We are unaware of any other study that has examined predictors of responsiveness to gefitinib-based therapy in patients with colorectal cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…Somewhat similar findings have been reported by others who have shown that sensitivity to TRAIL and resveratrol is reduced in p21-deficient cells (31), and in accordance with these results, cancer cells display increased sensitivity to TRAIL when arrested in the G 1 phase of the cell cycle (32,33). Thus, whereas induction of p21 is conventionally thought to promote cell survival (34), our studies and those of others suggest that p21 also has proapoptotic functions (35)(36)(37).…”
Section: Discussionsupporting
confidence: 92%
“…Related to this finding, recent research has indicated that Tomudex, another potent inhibitor of TS activity, induced p21 upregulation in human colorectal cancer cells, also through a p53-independent route, as did thymidine deprivation in TS deficient cells. 9 It is therefore possible that p21 upregulation may play a role in Pemetrexed-induced cell cycle arrest in myeloma cells sensitive to this compound. Temporally, after induction of cell cycle arrest, MM1S cells treated with Pemetrexed entered in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that p21 is upregulated in a p53-independent manner in the presence of TS inhibitors in human colorectal cancer cell lines, as did thymine deprivation in TS-deficient cells. 9 In the breast cancer line MCF7, and in the colon cancer cell lines HCT116 and RKO, Fas was involved in the induction of apoptosis in response to TS inhibitors. 10 More recently, it has been shown that Pemetrexed provoked dephosphorylation of AKT in human lung cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%